Minocycline Intravenous for the Treatment of Serious Infections Due to Gram-Negative Nonpseudomonal Bacteria, Including Stenotrophomonas maltophilia, Acinetobacter baumannii, and Burkholderia cepacia. Issue 4 (July 2020) - Sierra-Hoffman, Miguel; Redell, Mark; Benefield, Russell; Caruso, Patricia; Estrada, Sandy; Leuthner, Kimberly; Zappas, Kristie; Kennedy, Cynthia; Massey, Jill
Abstract : Background: Data on the role of minocycline intravenous (IV) in the treatment of serious gram-negative infections under real-world conditions are sparse. This study sought to provide evidence of real-world practices, including outcomes and safety. Methods: A multicenter observational study was conducted of 71 consecutive adult inpatients enrolled at 6 geographically diverse US hospitals between May 2015 and February 2018 who were treated with minocycline IV for gram-negative infections for at least 48 hours as monotherapy or combination therapy. Results: Infections included pneumonia (51%) and bacteremia (25%). The most prevalent gram-negative pathogens included Stenotrophomonas maltophilia (52%), Acinetobacter baumannii (30%), and Burkholderia complex (10%). In vitro susceptibility to minocycline was 100% for S. maltophilia . Clinical plus microbiologic response was observed in 80% of evaluable patients. Treatment of 29 evaluable patient infections due to S. maltophilia resulted in a clinical response rate of 79% and a microbiologic response rate of 72%. All patients with bacteremia due to S. maltophilia responded to minocycline IV. There were 17 (24%) in-hospital deaths of which 8 responded to minocycline. Minocycline was well tolerated. Conclusions: Minocycline demonstrated that high in vitro susceptibility against problematic gram-negative pathogens and administered as an IV formulation was associated with good clinical and microbiologic outcomes alone or in combination in a seriously ill patient population.